Functionalized metal-organic framework and MOF-derived materials for bone regeneration applications - Fan, Yuesen; Long, Chengbin; Cai, Yuyi; Hu, Yingkun; Peng, Lihua (Frontiers in Bioengineering and Biotechnology, 2025)
Bone defects resulting from trauma, tumors, infections, and aging present significant clinical challenges, with conventional grafts hindered by limitations in biocompatibility, mechanical strength, and integration. Metal-organic frameworks (MOFs), as advanced nanomaterials with tunable porosity, high surface area, and stimuli-responsive properties, hold immense potential for bone regeneration. This review provides a comprehensive overview of the classification, synthesis methods, osteogenic mechanisms, and applications of functionalized MOFs and their derivatives in bone repair. MOFs are classified based on structural topology, chemical composition, and functional applications. Synthesis techniques, including solvothermal, ultrasonic, and electrochemical approaches, are evaluated for customizing physical properties such as pore architecture and stability. Osteogenic mechanisms encompass enhancing implant physical characteristics to promote cell adhesion, sustained release of metal ions to activate signaling pathways, controlled drug delivery for targeted therapy, and anti-inflammatory/antioxidant effects through reactive oxygen species scavenging. Applications address various bone pathologies, demonstrating improved angiogenesis, osteointegration, and antibacterial performance in preclinical studies. Key challenges, including cytotoxicity, long-term biosafety, and scalability, are discussed, alongside strategies like surface modification and hybrid composites to overcome these barriers. Future perspectives focus on developing smart MOF-based scaffolds for personalized regenerative medicine, underscoring their transformative potential in orthopedic therapies.